Part I: Basic Considerations and Recommendations for Preparation, Measurement and Interpretation - G. Haroske; F. Giroud; A. Reith; A. Böcking (Analytical Cellular Pathology)
A task force of invited experts in the field of diagnostic DNA image cytometry, especially consisting of participants from the PRESS (Prototype Reference Standard Slides) and EUROPATH (European Pathology Assisted by Telematics for Healthcare) projects, but open to any other scientist or physician revealing experience in that new diagnostic procedure (names are given in the Annex A) agreed upon the following updated consensus report during the 5th International Congress of the ESACP 1997 in Oslo. This report is based on the preceeding one [9] and on results of the above mentioned European research projects. It deals with the following items: – Biological background and aims of DNA image cytometry,– Principles of the method,– Basic performance standards,– Diagnostic interpretation of DNA measurements,– Recommendations for practical use.